The Impact of Emotional Intelligence on Employee Performance - Jain, Tarun (Innovative Research Thoughts, 2018)
In recent years, the notion of emotional intelligence (EI) has exploded in the realm of management. The article analyses how organizational effectiveness correlates with EI. In the first section of the article, we provide a high-level introduction to EI and discuss its value in the business world. The research continues by discussing the ways in which EI's many aspects affect workers' productivity. Higher EI is associated with improved performance in areas such as work satisfaction, communication skills, and leadership abilities, according to the study's findings. Implications for management practices are discussed towards the end of the study. These include the value of recognizing and nurturing workers' EI abilities.